Description of Home Conditions Based on Healthy Home Standards for Toddlers with Acuate Respiratory Tract Infections (ARI) - Natasya, Saruli; Tampubolon, Nurhannifah Rizky; Amir, Yufitriana; Novayelinda, Riri; Fitri, Aminatul (Jurnal Keperawatan Profesional, 2025)
Healthy home conditions based on healthy home standards for toddlers with ARI. This study used a descriptive observational design. The study sample consisted of 67 respondents selected based on inclusion criteria, namely parents of toddlers diagnosed with ARI using the accidental sampling technique. The questionnaire used was a healthy home assessment. The analysis used was univariate data analysis. There were 62.7% of respondents in early adulthood (26-35 years old), 47.8% of toddlers (12-59 months old), and 50.7% of male children. Of the 67 respondents, 59.7% of respondents' homes met the healthy home criteria and 40.3% of respondents' homes did not meet the healthy home criteria. In terms of housing components, 88.1% had permanent ventilation <10% of the floor area of the house, 56.7% of respondents' homes did not have a kitchen smoke vent, In terms of sanitation facilities, 100% of waste was discharged into open gutters, and in terms of resident behavior, 92.5% sometimes opened their bedroom windows and 91% sometimes opened their living room windows, while 95.5% sometimes cleaned their yards. In conclusion, some of the houses met the requirements for healthy housing, while others did not. The majority of the houses, sanitation facilities, and residents' behavior were found to be good.